Pemberian Sanksi terhadap Masyarakat yang Melanggar Adat dalam Perkawinan Studi Nagari Persiapan Sundata Selatan, Kecamatan Lubuk Sikaping Kabupaten Pasaman - Dewantri Putri (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2020)
Abstract : Every human have social life.They also have marriage life with rules and norms. It divided become traditional and law ofrules and norms. Sometime, people break it, so they will get punishment. The research objectives are: 1) Describe the form of sanctions given by traditional leaders to perpetrators of marriage customs violations that are not in accordance with the prevailing manners in NagariPersiapanSundata Selatan; 2) Describe the causes of marriages that do not follow the tradional way of NagariPersiapanSundata Selatan. This research use social control theory from Walter Reckles. Heexplain about two control systems. The first is internal control and the second is external control, in which the inner control is the human mind or conscience and from the outside it can be in the form of family, neighbors, police or authorities. This research usequalitative method with a descriptive type. This researchuse purposive sampling technique and data collection use observation and in-depth interviews. The informants in this study were people who had violated customs in matters of marriage, ninikmamak, and the perpetrators' neighbors. The forms of marital custom violations committed by the community in marriage in the NagariPersiapan of Sundata Selatan, namely: ethnic marriage, “kawinlari” and